Impact of Intrinsic Motivational Practices on Performance in Secondary School Teachers: A Cross-sectional Study in Mbarara City, Uganda - Bato, Annet; Ayebare, David S.; Rukundo, Aloysius; Mwesigye, Adrian (Asian Education, 2024)
Performance of secondary school teachers is sequential to intrinsic motivational practices, particularly among teachers experiencing financial strain across global in various contextual settings. This study investigated the contributions of intrinsic motivational practices on performance of teachers in the secondary schools in the Mbarara City. Descriptive cross-sectional design using a quantitative approach was conducted in January 2012 among 108 teachers in Mbarara City. Pearson product-moment correlations and linear regression were conducted using Stata 15. The study findings were that intrinsic motivational practices had a perfect positive impact on performance of secondary school teachers in Mbarara City (r = .0.925, p <0.01) and explained only 85.5% of the variance of performance of the secondary school teachers in Mbarara City (r2 = .855). Therefore, various intrinsic motivational practices influence performance of the secondary school teachers. Strategies for that enhance intrinsic motivational practices are paramount.
Keywords: Performance; Intrinsic motivational Practices; Secondary School Teacher; Secondary School; Mbarara City; Uganda